2002
DOI: 10.1159/000058309
|View full text |Cite
|
Sign up to set email alerts
|

An Animal Model of Auditory Cortex Prostheses

Abstract: Experiments aimed at rehabilitating deaf and blind patients with cortical prostheses were first conducted decades ago, but epicortical electrodes allowed only crude information transfer. Here we report that in Mongolian gerbils with electrodes implanted in input layers of the primary auditory cortex, spatial, temporal and spatiotemporal variations in intracortical stimulation all lead to perceptual differences as evidenced by discrimination training. For some stimulus regimes discrimination learning was as fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Cortical stimulation paradigms can take advantage of the spatial topography of cortical representations, which underlie visual (Dobelle and Mladejov 1974; Bak et al 1990; Schmidt et al 1996; Troyk et al 2003a, b; Tehovnik et al 2004, 2005), somatosensory (Talwar et al 2002; Rousche et al 2003; Ohara et al 2004), and auditory sensations (Rousche and Normann 1997; Rauschecker and Shannon 2002; Scheich and Breindl 2002; Rousche et al 2003; Otto et al 2005). The artificial sensations induced by electrical stimulation have been shown to elicit responses that are indicative of the mapped topographical location of the corresponding sensory inputs (Romo et al 2000; Troyk et al 2003b; Tehovnik et al 2004, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Cortical stimulation paradigms can take advantage of the spatial topography of cortical representations, which underlie visual (Dobelle and Mladejov 1974; Bak et al 1990; Schmidt et al 1996; Troyk et al 2003a, b; Tehovnik et al 2004, 2005), somatosensory (Talwar et al 2002; Rousche et al 2003; Ohara et al 2004), and auditory sensations (Rousche and Normann 1997; Rauschecker and Shannon 2002; Scheich and Breindl 2002; Rousche et al 2003; Otto et al 2005). The artificial sensations induced by electrical stimulation have been shown to elicit responses that are indicative of the mapped topographical location of the corresponding sensory inputs (Romo et al 2000; Troyk et al 2003b; Tehovnik et al 2004, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In animal models it has been shown that electrically evoked percepts vary in accordance with the location of the stimulation site within retinotopic (Bradley et al, 2005), tonotopic (Scheich and Breindl, 2002;Otto et al, 2005), and somatotopic (Leal-Campanario et al, 2006;Fitzsimmons et al, 2007) map representations. Several studies have specifically demonstrated that psychophysical properties of electrically evoked percepts can be linked to the representational topographies of cortical maps at the stimulation site (Romo et al, 2000;Bartlett et al, 2005), in some cases even to tuning properties of small sets of directly excited neurons located within one or a few cortical columns (Tehovnik et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, beyond the local encoding of stimulus features, learning plays an important role, as by learning, meaning is attributed to the electrical stimuli (Scheich and Breindl, 2002;Bradley et al, 2005;Fernández et al, 2005;Leal-Campanario et al, 2006). When animals learn to discriminate or categorize natural, e.g., visual, auditory, or somatosensory stimuli, large-scale stimulus-specific patterns emerge from the ongoing activity of sensory cortex as has been demonstrated by recording electrocorticograms (ECoGs) at high spatial resolution (Barrie et al, 1996;Freeman, 2000;Ohl et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…One proposed application of cortical microstimulation is utilization in a sensory cortical prosthesis. Some possible prosthetic sensory interface areas are the visual cortex for blindness (Bak et al, 1990;Schmidt et al, 1996;Troyk et al, 2003), and the auditory cortex for deafness Rousche and Normann, 1999;Rousche et al, 2003;Scheich and Breindl, 2002), although a somatosensory cortical prosthesis may be equally likely. In order to develop these neuroprosthetic systems to fruition, optimization of device parameters such as total electrode count, inter-electrode spacing and the effects of patterned stimulation require investigation.…”
Section: Introductionmentioning
confidence: 99%